Effects of grape seed extract supplementation on the growth performance, nutrients digestion and immunity of weaned lambs - Ma, Jian; Li, Tao; Lin, Lu; Lu, Yuezhang; Chen, Xi; Li, Sibing; Du, Chunmei; Wei, Chen; Yin, Fuquan; Gan, Shangquan (Frontiers in Veterinary Science, 2024)
Grape seed extract (GSE) has a variety of biological functions. At present, there has been limited information on the utilization of GSE as a feed additive in weaned lambs. The aim of this experiment was to study the potential influence of dietary supplementation with GSE on the growth performance, rumen fermentation characteristics, apparent digestibility, blood parameters and immunity in weaned lambs. In total, 30 male Hu sheep lambs with similar body weight (15.43 ± 0.49 kg) and age (48 ± 2 days) were randomly divided into two treatments: control (CON, fed basal ration) and GSE [fed basal ration and 0.6 g/d GSE (main compositions: proanthocyanidin 50%, catechin 24%, gallic acid 16% and epicatechin 6%) per lamb]. The feeding experiment lasted for 60 d. Results showed that GSE supplementation significantly increased (p = 0.008) the average daily gain of lambs. Compared with CON group, the ruminal propionate and butyrate concentrations were significantly increased (p < 0.05) in GSE group, whereas the ammonia nitrogen was decreased (p = 0.007). Also, the crude protein, neutral detergent fiber and ether extract digestibility of GSE group were higher (p < 0.05) than those of CON group. The serum contents of glucose, triglyceride, immunoglobulin G, glutathione peroxidase and total antioxidant capacity were significantly increased (p < 0.05) in GSE group when compared to those in CON group. However, an opposite trend of urea nitrogen, non-esterified fatty acid, interleukin-1β, itumor necrosis factor-α and malondialdehyde was observed between the two groups. Additionally, supplementation of GSE increased (p < 0.05) the Lactobacillus and decreased (p < 0.05) the Escherichia coli and Salmonella counts in the feces of lambs. In summary, GSE supplementation can improve growth performance, nutrient digestion and immunity of weaned lambs.